Model Studi Hukum Keluarga Islam: Mencari Pijakan, Merespon Tantangan Zaman - JM Muslimin (JURNAL INDO-ISLAMIKA, 2017)
This article offers a contextual study model on the Islamic law in Indonesia where Muslim people expect their religion to be able to adapt to the complex current developments, such as administrative affairs and state legislations, in the country. This issue also takes place globally, particularly in the Muslim world. Here, this paper delves this problem by exploring some factors that lead people to partake that expectation.